Perfil Lipidico, Antropométrico y de Condición Física de la Selección de Porrismo de la Universidad del Quindio (2016)
The Cheerleading is a sport that is increasingly boom in the country, the University of Quindío nown how lipid profile level, anthropometric and physical fitness these athletes profile are. Objective is: Set the lipid, anthropometric and physical fitness of students from the cheerleading team of the University of Quindío profile. Methodology: The study was quantitative, descriptive, cross-sectional, was performed on the members of the cheerleading team at the University of Quindío, which is made up of 18 members (12 are men and 6 women), anthropometric assessment was performed following the indications of the International Society for the Advancement of Ki anthropometry (ISAK) and for determination of the physical abilities test Wells, Legger, acceleration and horizontal jump 30m were used. Results: A general level athletes have a lipid profile within the normal range with the exception of HDL that are below, some athletes also have cholesterol and triglyceride levels above normal. Anthropometric both BMI level as in the ICC are at the desired levels, but the fat percentage is high in both sexes and much more in men. The somatotype predominant in women was the mesomorph-balanced while in men was the meso endomorph. the level of physical capabilities women have greater flexibility with respect to men but have deficits in other capacities, in the case of men have adequate strength but poor performance in other capacities Conclusions: Although a general level the lipid profile is fine, there are several athletes with altered values, the fat percentage is higher for athletes and is mostly increased in men. The overall selection must modify your workout to improve conditional abilities.